Inflammatory Pseudotumors of the Skull Base: Meta-Analysis. Issue 8 (September 2015) - Alyono, Jennifer C.; Shi, Yangyang; Berry, Gerald J.; Recht, Lawrence D.; Harsh, Griffith R.; Jackler, Robert K.; Corrales, C. Eduardo
Abstract : Objective: To describe the presentation, treatment, and outcome of inflammatory pseudotumors (IPs) of the skull base. Data Sources: English-language articles in PubMed, Web of Science, and EMBASE from earliest available through April 2014. Study Selection: Articles were identified using a keyword search for "inflammatory pseudotumor, " "inflammatory myofibroblastoma, " or "plasma cell granuloma, " including a keyword localizing to the skull base. Data Extraction: One hundred papers with 157 cases met inclusion criteria. History, tumor site, initial and subsequent treatment, outcomes, and complications were extracted. Student t test, z test, and analysis of variance were used to analyze demographics, symptoms, sites involved, and outcomes. Odds ratios for site versus initial treatment were calculated. Data Synthesis: At diagnosis, average patient age was 41 years. Approximately 70% of lesions primarily involved the anterior skull base, 29% the lateral skull base, and 1.2% the occiput. The most common initial treatments were steroids (44%), surgery (28%), and surgery with steroids (16%). Anterior lesions were 55.8 times more likely than lateral lesions to be treated initially with steroids (CI, 14.7–212). Seventy-six percent of patients had stable or resolved symptoms after a single course of treatment. Conclusion: Diagnosis of skull base IP requires ruling out other aggressive pathologies, such as malignancy and infection, and maintaining a high index of suspicion. Surgery is favored for lesions that can be removed in toto with minimal morbidity, as well as steroids for those sites where anatomy limits complete resection, such as within the orbit, cavernous sinus, or brain. An option for larger lesions involving vital anatomy is debulking, followed by postoperative steroids. Abstract : Supplemental digital content is available in the text.